Synthesis, Characterization, X-ray crystallography, acetyl cholinesterase inhibition and antioxidant activities of some novel ketone derivatives of gallic hydrazide-derived schiff bases - Gwaram, N.S.; Abdelwahab, S.I.; Khaledi, H.; Hassandarvish, P.; Hadi, A.H.A.; Yehye, W.A.; Alhadi, A.A.; Othman, R.; Chung, L.Y.; Sukumaran, S.D.; Buckle, M.J.C.; Abdulla, M.A.; et al. (2012)
Alzheimer's disease (AD) is the most common form of dementia among older people and the pathogenesis of this disease is associated with oxidative stress. Acetylcholinesterase inhibitors with antioxidant activities are considered potential treatments for AD. Some novel ketone derivatives of gallic hydrazide-derived Schiff bases were synthesized and examined for their antioxidant activities and in vitro and in silico acetyl cholinesterase inhibition. The compounds were characterized using spectroscopy and X-ray crystallography. The ferric reducing antioxidant power (FRAP) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) assays revealed that all the compounds have strong antioxidant activities. N-(1-(5-bromo-2-hydroxyphenyl)-ethylidene)-3,4,5-trihydroxybenzohydrazide (2) was the most potent inhibitor of human acetyl cholinesterase, giving an inhibition rate of 77% at 100 mu M. Molecular docking simulation of the ligand-enzyme complex suggested that the ligand may be positioned in the enzyme's active-site gorge, interacting with residues in the peripheral anionic subsite (PAS) and acyl binding pocket (ABP). The current work warrants further preclinical studies to assess the potential for these novel compounds for the treatment of AD.